Normative Harmonization: The Eclecticism of Talak Law as a Compromise between Islamic Legal Principles and Indonesian Legislation - Khasan Alimudin; M. Rifa Jamaludin Nasir (QURU’: Journal of Family Law and Culture, 2024)
This article discusses the validity and legal consequences of divorce in Islamic law and positive law in Indonesia. This research uses a qualitative approach with deductive analysis method and literature study with Normative-Juridical approach. The results show that divorce is considered valid in Islamic law if it fulfills the predetermined conditions. On the other hand, in Indonesian positive law, divorce is recognized as valid if it is carried out through a court hearing process in accordance with Law No. 1 of 1974 concerning Marriage. In terms of post-divorce legal consequences, both Islamic law and Indonesian positive law regulate the rights, positions and obligations of former husbands and wives. Indonesian positive law, particularly in relation to divorce, has undergone legal eclecticism, incorporating the principles of legality, justice and humanity. Meanwhile, in the context of Islamic law, these principles are manifested in the concept of mashlahat, which covers five aspects, namely the maintenance of religion, soul, mind, offspring, and property.